Educação, território e governação: o programa aproximar e a terceira margem - Alves, José Matias (2017)
Th is text elects as an object of analysis the Program “Aproximar Educação” (decentralization of educational competencies to the local power) and its execution in the 15 municipalities that were invited by the government to join the program. A brief content analysis of the Ministerial Resolution is done, as well as a generic analysis of the 15 interadministrative contracts of competency delegation, particularizing two of them and trying to analyse the distribution of power between the centre and the peripheries, including the municipality, the municipal council of education and the school grouping. It is sustained that, in the fi eld of the orientations towards action, the political will to institute a new local governance model, which we designate as socio communitarian regulation, is visible, although it cannot be generalized. Some critical discourses that look at this process as a way of contributing to take away the State’s responsibility, of “privatizing” education and of municipalisation are summarily analysed. It can be concluded that the development of this Program has inscribed itself in a paradigm of confl ict of visions, powers and counter powers, what contributes to the uncertainty of its future.